2022
DOI: 10.29271/jcpsp.2022.11.1415
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Volume Ratio of Subchorionic Hematoma to Gestation SAC in First-trimester and Pregnancy Outcome of Patients with Threatened Abortion

Abstract: Objective: To find the relationship between the volume ratio of subchorionic hematoma (SCH) to gestation sac measured by three--dimensional ultrasound and pregnancy outcome of patients with threatened abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Therefore, more objective and accurate imaging methods are needed to quantify SCH size and study the effect of SCH on pregnancy outcomes. The evaluation of SCH size, measured only in a single plane, or calculating the volume using an ellipsoid formula, cannot accurately evaluate SCH with an irregular shape, while the reconstruction and measurement of SCH volume with VOCAL technology, which is less affected by morphological irregular factors, can more accurately and reliably react to SCH volume[ 18 , 19 ]. This study introduced the following three parameters: Ss/Sg, Vs/Vg, and 3DVs/3DVg, and the results showed that the greater the ratio of the three, the greater the risk of adverse pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, more objective and accurate imaging methods are needed to quantify SCH size and study the effect of SCH on pregnancy outcomes. The evaluation of SCH size, measured only in a single plane, or calculating the volume using an ellipsoid formula, cannot accurately evaluate SCH with an irregular shape, while the reconstruction and measurement of SCH volume with VOCAL technology, which is less affected by morphological irregular factors, can more accurately and reliably react to SCH volume[ 18 , 19 ]. This study introduced the following three parameters: Ss/Sg, Vs/Vg, and 3DVs/3DVg, and the results showed that the greater the ratio of the three, the greater the risk of adverse pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual organ computer-aided analysis (VOCAL) is a method to reconstruct the shape of tissues and organs and automatically and accurately measure the volume, which can avoid the measurement error of two-dimensional (2D) ultrasound to a certain extent. VOCAL technology has been applied to volumetric measurements of various organs and tissues, such as in obstetrics, to evaluate fetal brain structure[ 14 , 15 ], fetal heart[ 16 ], gestational sac[ 17 ], hematoma[ 18 , 19 ], and placental volumes[ 20 ]. However, few studies have evaluated the volume of SCH and early pregnancy outcomes using VOCAL technology, and progesterone can reflect fetal growth and abortion.…”
Section: Introductionmentioning
confidence: 99%